Aplikasi Virtual Tour 360° Sebagai Media Pengenalan Desa Wisata Edukasi Kopi Cupunagara, Subang - Sherinatasha Firmansyah Rani; Vanessa Vanessa; Syifa Younna Rhapsodio; Any Ariani Noor (Program Studi Pariwisata - Universitas Internasional Batam, 2021)
In the midst of the COVID-19 pandemic problem which indirectly limits people's physical activities, this has resulted in a drastic decrease in the volume of people and goods. The use of the Virtual Tour 360 ° application technology can be used to overcome promotional problems due to the impact of the COVID-19 pandemic, as well as be a positive value and alternative for the field of work. The Virtual Tour 360 ° application itself is a simulation of a real location consisting of several videos and photographic media, to provide the experience of visiting a location just by looking at the monitor screen. The design of this virtual tour application idea requires support from various parties, especially local governments, managers and application developers so that it can be implemented and released properly. With this idea, it is hoped that it can become an additional means of traveling for tourists and introduce desa wisata edukasi Kopi Cupunagara easily, quickly, and relevant. Keywords: Virtual Tour 360°, Educational Tourism Village Kopi Cupunagara, Promotion